Pelatihan Pemurnian Pektin Dari Kulit Buah Sukun Di Kota Padang Sumatera Barat - Rizal, Rosiana; Afriyeni, Helmice; Brigita, Brigita; Antonio, Antonio; Wulandari, Eka; Bakri, Leady Permanda (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Community service activities have been carried out on the isolation and purification of pectin compounds from breadfruit peels grown in Padang City, West Sumatra Province to improve farmer commodities regarding the availability of quality pectin raw materials. This service aims to determine the effect of purification training on the quality of the pectin produced. Pectin extraction was carried out by the reflux method from dried breadfruit peels with 0.1 N HCl solvent with a pH of 1.5 and extracted for 150 minutes. The quality characteristics of breadfruit peel pectin in Padang City include an equivalent weight of 3,168.5 mg; methoxyl content of 3.26%; galacturonic acid content of 96.27%. The conclusion of this activity is that the material is suitable for the needs so that it can improve the economy of breadfruit farmers and standardize pectin as a raw material for making capsule shells. There was a positive response from the participants considering that the service activity was part of the partners' understanding of the use of pectin as a raw material. Most (60%) of participants understood the actions taken by partners to improve the quality of pectin.